Analisis Tingkat Efisiensi pada Konfigurasi Mikrotik Hotspot menggunakan Metode Zero Touch Provisioning - Fariz Fariz; Henry Saptono; April Rustianto (Jurnal Informatika Terpadu, 2021)
ZTP (Zero Touch Provisioning) is an innovation in the IT world, which changes configuring devices from manual to automatic. This innovation creates due to the increasing need for network devices. It is a challenge for network companies to manage it both in terms of time and cost. In the traditional method, Network device administration must log in to each network device one by one to perform configuration. This is, of course, inefficient. This is where the advantages of automation, network device configuration becomes more efficient, plus repetitive work such as configuration backups monitoring can do automatically. In this study, the authors will test the efficient use of the ZTP by comparing the configuration time manually and automation with ZTP. This research configures the IP address, creates a DHCP server, and creates a hotspot on MikroTik. To make it easier for network management, the author created a dashboard to find out which devices have been configured. The automation system itself makes using Python programming, which utilizes the Paramiko main library as a liaison between network devices and automation servers via the SSHv2 protocol.